Fibrotic microRNAs in the suppression of HSC activation and ECM deposition to facilitate the regression of hepatic fibrosis in zebrafish - Yu-Heng Lai; Mu-Kuang He; Chung-Tsui Huang; Han-Yu Tseng; Tzu-Ching Lin; Ting-Yu Yang; Semon Wu; Guor Mour Her (Journal of Molecular Medicine, 2026)
During liver injury, early pathological changes may go unnoticed, delaying the diagnosis until the disease has advanced to stages such as fibrosis, cirrhosis, or hepatocellular carcinoma. Hepatic fibrosis is a sign of long-term liver injury that leads toward permanent liver damage. It involves the buildup of too much extracellular matrix (ECM) and is activated by hepatic stellate cells (HSCs). The transforming growth factor-β1 (TGF-β1)/SMAD pathway is central to this process, which shows great potential for therapeutic strategies. Therefore, we investigated the therapeutic potential of microRNA (miRNA)-mediated regulation of fibrogenesis by using zebrafish models. A group of fibrosis-related miRNAs was identified and used to generate transgenic zebrafish lines. Fibrosis was induced via doxycycline (DOX)-controlled overexpression of TGF-β1a, and the antifibrotic efficacy of miRNAs was evaluated. Quantitative real-time PCR showed a marked downregulation of the target miRNAs, accompanied by decreased expression of fibrotic markers. Next, we confirmed that TGF-β1a, GREM1, and α-SMA protein levels were decreasing. Histological staining revealed improved liver structure and diminished collagen deposition. These findings indicate that through manipulating the miRNA expressions, we can effectively disrupt TGF-β-induced fibrogenesis, inactivate HSC, inhibit ECM remodeling, and attenuate liver fibrosis, and highlight the potential of miRNA-based therapeutic strategies for early intervention in liver disease. Key messages Establishment of an in vivo model for developing an inducible miRNA expression system in zebrafish. Predicting and evaluating targeted miRNAs that attenuate TGF-β-induced hepatic fibrosis. Elucidate the potential mechanism for fibrosis that may be a strategy for future therapies. Graphical Abstract MicroRNA-mediated modulation attenuates hepatic fibrosis by coordinately suppressing the TGF-β/SMAD signaling pathway, hepatic stellate cell activation, and extracellular matrix deposition. Protein-level validation confirms reduced phosphorylation of Smad2 and decreased expression of key fibrotic markers, including α-SMA, collagen I, and fibronectin. These findings highlight a multi-target regulatory mechanism through which miRNAs exert antifibrotic effects at the systems level.

Isolation and food-relevant evaluation of a novel lytic Kayfunavirus phage vB-EcoP-B10 for controlling STEC on food-contact surfaces and in raw beef - Yuxin Mu; Min Li; Xiangqi Bai; Qianhong Li; Xiaodong Xia; Ting Zhou; Chunling Zhang; Ying Yu; Yanna Dai; Jifeng Pu; Hu Pan; Xin Wang (Food Research International, 2026)

Airborne microplastics as concentrators of anthropogenic heavy metals: Differentiation of intrinsic additive-derived metals and post-emission enrichment - Wahyu Diah Proborini; Chun-Hsuan Wei; Chun-Hung Ku; Wei-Ting Hsu; Mu-Jean Chen; Hsiu-Chuan Chou; Yu-Cheng Chen (Journal of Hazardous Materials, 2026)

Development and application of KASP molecular marker for accelerated breeding of low-acid Cerasus humilis cultivars - Xia-Yu Xing; Xiao-Yan Wang; Yue-Zhan Xiao; Hao-Nan Wang; Hou-Qiang Song; Ming Liu; Xiao-Peng Mu; Jian-Cheng Zhang; Lu-Ting Jia; Yu Gary Gao; Shuai Zhang; Peng-Fei Wang (Plant Cell Reports, 2026)

Two undescribed benzofuran derivatives from chaetomium elatum - Chen-Yi Yan; Feng Ju; Yu-Hui Chen; Yu-Ting Mu; Yun-Jie Hu; Da-Le Guo; Yun Deng; Qi-Xuan Kuang (Natural Product Research, 2026)

Efficient fabrication of PLA/PBAT/ZnO films with inverted-pyramid Micro/nanostructures for robust anti-wet pack and antimicrobial protection - Yu Du; Rong Zhou; Kai Mu; Congyuan Zhang; Changjun Guo; Jiabao Lu; Zihao Li; Heng Xie; Ting Wu; Jinping Qu (Chemical Engineering Journal, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

A novel antioxidant peptide DD12 (DWPDARGIWHND) derived from dry cured ham alleviates H2O2-induced oxidative damage via the Keap1-Nrf2-ARE pathway - Ying-dao Nan; Si-qi Chen; Guan-hao Li; Ting-yu Li; Bai-de Mu; Juan Wang; Jian Feng; Hong-mei Li; Chun-xiang Piao (Food Research International, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A pair of lignans isolated from Trachelospermum jasminoides and their anti-inflammatory activity - Chen-Yi Yan; Miao Wang; Yu-Ting Mu; Li-Lian Zhao; Yu-Liang Guo; Wei-Zhen Dong; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2025)

Using Interactive Multi-Media Panorama Virtual Reality to Balance Heritage Science, Education and Conservation At Zhoukoudian, Fangshan UNESCO Global Geopark - Jun-Ting Qiu; Tong-Yu Zhang; Lixian Tian; Xin-Min Rui; Hong-Xu Mu; Liang Qiu; Long-Xin Xu (Geoheritage, 2025)

Synergistic recovery for Al and Ga within high-alumina fly ash by carbochlorination using the response surface method - Wang Long; Zhao Xin-xin; Zhang Zi-mu; Zhang Ting-An; Lv Guo-Zhi; Dou Zhi-He; Liu Yan; Fan zhi-yu (Waste Management, 2025)

Efficient fabrication of hunting trap-inspired degradable film with enhancing antimicrobial activity and reducing fomite transmission - Yu Du; Kai Mu; Xiaolong Li; Cheng Li; Chao Ding; Pingxu Chen; Ting Wu; Heng Xie; Jinping Qu (Journal of Hazardous Materials, 2025)

Activation of NR2A-Wnt-TLR2 Signaling Axis in Satellite Glial Cells of the Dorsal Root Ganglion Contributes to Neuropathic Pain Induced by Nerve Injury in Diabetic Mice - Yan-Yan Zhang; De-Xin Zhu; Mu-Yun Wang; Ya-Ting Yi; Yu-Heng Feng; Cheng Zhou; Chun-Jie Li; Fei Liu; Jie-Fei Shen (Molecular Neurobiology, 2025)

Fabrication of a high strength, swelling resistance, and conductive hydrogel for flexible underwater sensor via ketalization - Kejun Zhong; Jie Xiang; Yu Liu; Chuanlin Song; Yuetong Mu; Ting Yao; Kai Zhao; Tianfeng Gu; Pengxiang Jia; Wenyan Zhang (Chemical Engineering Journal, 2025)

A β-cyclodextrin-based supramolecular photonic crystal hydrogel biosensor with macroporous structures for naked-eye visual detection of cholesterol - Xi Wang; Jingjing Mu; Junjie Ren; Hairong Yu; Xingbin Lv; Ting Liang; Changjing Cheng (Carbohydrate Polymers, 2025)

Combined application of multi-omics techniques and multivariate statistical analysis reveals the core functional microorganisms of Qula in Tibet, China - Ying Huang; Jiarong Li; Ting Li; Xingxing Deng; Qihong Zhong; Dezheng Wu; Zehuan Liu; Dawa Zhaxi; Yu Mu (Food Bioscience, 2024)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

A systematic investigation of PVDF-HFP in perovskite solar cells for improved space mission reliability - Seoungjun Ahn; Wei-Hao Chiu; Wei-Chen Chu; Pei-Yu Chen; Ting-Han Lin; Kun-Mu Lee (Chemical Engineering Journal, 2024)

Surface functional groups on nanoplastics delay the recovery of gut microbiota after combined exposure to sulfamethazine in marine medaka (Oryzias melastigma) - Yu Ting Zhang; Zhi Zhang; Mingdong Zhang; Chaoyue Zhang; Hongxing Chen; Feipeng Wang; Lingtian Xie; Jingli Mu (Aquatic Toxicology, 2024)

Incomplete recovery of gut microbiota in marine medaka (Oryzias melastigma) during the depuration phase, after exposure to sulfamethazine/nanoplastics - Feipeng Wang; Chaoyue Zhang; Shujie Cai; Jingyu Yang; Faguang Li; Xiaofan Liu; Yu Ting Zhang; Jingli Mu (Science of The Total Environment, 2023)

Correction: Three-Dimensional Digital Reconstruction of the Cerebellar Cortex: Lobule Thickness, Surface Area Measurements, and Layer Architecture - Junxiao Zheng; Qinzhu Yang; Nikos Makris; Kaibin Huang; Jianwen Liang; Chenfei Ye; Xiaxia Yu; Mu Tian; Ting Ma; Tian Mou; Wenlong Guo; Ron Kikinis; et al. (The Cerebellum, 2023)

A seminal perspective on the role of chondroitin sulfate in biomineralization - Jia-xin Hao; Qian-qian Wan; Zhao Mu; Jun-ting Gu; Wei-wei Yu; Wen Qin; Yu-tao Li; Chen-yu Wang; Yu-xuan Ma; Kai Jiao; Franklin Tay; Lina Niu (Carbohydrate Polymers, 2023)

Polylactic acid (PLA), polyethylene terephthalate (PET), and polystyrene (PS) microplastics differently affect the gut microbiota of marine medaka (Oryzias melastigma) after individual and combined exposure with sulfamethazine - Chaoyue Zhang; Faguang Li; Xiaofan Liu; Lingtian Xie; Yu Ting Zhang; Jingli Mu (Aquatic Toxicology, 2023)

Model development and validation of personal exposure to PM2.5 among urban elders - Wei-Ting Hsu; Chun-Hung Ku; Mu-Jean Chen; Chih-Da Wu; Shih-Chun Candice Lung; Yu-Cheng Chen (Environmental Pollution, 2023)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Efficient degradation of semi-coking wastewater in three-dimensional electro-Fenton by CuFe2O4 heterocatalyst - Wen-wen Gao; Ting Su; Wei Zhao; Zhi-fang Zhang; Miao Mu; Yong-hui Song; Xue-xue Zhang; Xin-yu Liu (Environmental Science and Pollution Research, 2022)

Three-Dimensional Digital Reconstruction of the Cerebellar Cortex: Lobule Thickness, Surface Area Measurements, and Layer Architecture - Junxiao Zheng; Qinzhu Yang; Nikos Makris; Kaibin Huang; Jianwen Liang; Chenfei Ye; Xiaxia Yu; Mu Tian; Ting Ma; Tian Mou; Wenlong Guo; Ron Kikinis; et al. (The Cerebellum, 2022)
The cerebellum is ontogenetically one of the first structures to develop in the central nervous system; nevertheless, it has been only recently reconsidered for its significant neurobiological, functional, and clinical relevance in humans. Thus, it has been a relatively under-studied compared to the cerebrum. Currently, non-invasive imaging modalities can barely reach the necessary resolution to unfold its entire, convoluted surface, while only histological analyses can reveal local information at the micrometer scale. Herein, we used the BigBrain dataset to generate area and point-wise thickness measurements for all layers of the cerebellar cortex and for each lobule in particular. We found that the overall surface area of the cerebellar granular layer (including Purkinje cells) was 1,732 cm 2 and the molecular layer was 1,945 cm 2 . The average thickness of the granular layer is 0.88 mm (± 0.83) and that of the molecular layer is 0.32 mm (± 0.08). The cerebellum (both granular and molecular layers) is thicker at the depth of the sulci and thinner at the crowns of the gyri. Globally, the granular layer is thicker in the lateral-posterior-inferior region than the medial-superior regions. The characterization of individual layers in the cerebellum achieved herein represents a stepping-stone for investigations interrelating structural and functional connectivity with cerebellar architectonics using neuroimaging, which is a matter of considerable relevance in basic and clinical neuroscience. Furthermore, these data provide templates for the construction of cerebellar topographic maps and the precise localization of structural and functional alterations in diseases affecting the cerebellum.

Comparative phylogeography of Acanthocalyx (Caprifoliaceae) reveals distinct genetic structures in the Himalaya–Hengduan Mountains - Qi-Yong Mu; Chih-Chieh Yu; Yan Wang; Ting-Shen Han; Hui Wang; Wen-Na Ding; Qiu-Yue Zhang; Shook Ling Low; Quan-Jing Zheng; Chuan Peng; Zheng-Yan Hu; Yao-Wu Xing (Alpine Botany, 2022)

Placebo effect of rTMS on post-stroke motor rehabilitation: a meta-analysis - Yu Jin; Ting Pu; Zhiwei Guo; Binghu Jiang; Qiwen Mu (Acta Neurologica Belgica, 2021)

Geosites in Karamay city, Xinjiang Uygur Autonomous Region, northwest China - Jun-Ting Qiu; Liang Qiu; Hong-Xu Mu; Wen-Xin Yang; Feng Chen; Bo-Kun Yan; Jun-Chuan Yu; He-Ming Yang (Geoheritage, 2019)

Measurement of urinary arsenic profiles and DNA hypomethylation in a case–control study of urothelial carcinoma - Chi-Jung Chung; Hui-Ling Lee; Chao-Hsiang Chang; Han Chang; Chiu-Shong Liu; Wei-Ting Jung; Huei-Ju Liu; Saou-Hsing Liou; Mu-Chi Chung; Yu-Mei Hsueh (Archives of Toxicology, 2019)

Dose Verification for Tumor Motion with Different Treatment Planning Systems: A Dynamic Thorax Phantom Study - Shih-Neng Yang; Chun-Wei Lin; Mu-Bai Chang; Geoffrey G. Zhang; Kuei-Ting Chou; Yu-Rou Chiou; Shung-Shung Sun; Louis Lui; Tsung-Jung Ho; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Reactive Oxygen Species-mediated Loss of Phenotype of Parvalbumin Interneurons Contributes to Long-term Cognitive Impairments After Repeated Neonatal Ketamine Exposures - Hui Zhang; Xiao-ru Sun; Jing Wang; Zhen-zhen Zhang; Hong-ting Zhao; Hui-hui Li; Mu-huo Ji; Kuan-yu Li; Jian-jun Yang (Neurotoxicity Research, 2016)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)